PhET Aplication Program: Strategi Penguatan Pemahaman Pembelajaran Jarak Jauh pada Materi Radiasi Benda Hitam melalui Percobaan Berbantu Lab Virtual dan Media Sosial - Ida Puspita (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to improve the understanding of black matter radiation by utilizing the PhET circuit-construction-kit-ac application in remote learning using Whatsapp social media, as well as utilizing virtual labs. This article is the best practice carried out in the even semester of 2019/2020 lesson in the students of the class XII IPA. The implementation of this learning strategy has a positive achievement, among others: 1) understanding and problem solving black objects radiation with distance learning becomes easier; 2) as a solution for conducting experiments in the application of distance learning that can be done online or offline; 3) can display real and visual radiation experiments of black objects and easy to operate; 4) Use of PhET circuit-construction-kit-ac based on basic concepts, rules or principles, prevailing agreements, and use of reasoning; 5) There are no constraints while implementing PhET circuit-construction-kit-ac in distance learning; 6) Training students' independence. The results showed: a) the presence of test solutions in distance learning; b) Students are more enthusiastic, with indications of collecting timely assignments, all the tasks provided completed by all students; c) Students can match the final test results using the PhET circuit-construction-kit-ac with qualitative calculations using the prevailing black-object radiation equation; and d) The increasing learning outcomes are quite significant.